KORELASI PENGUASAAN KOSAKATA BIDANG LINGKUNGAN HIDUP DENGAN MENULIS KARANGAN ARGUMENTASI TENTANG LINGKUNGAN HIDUP - Guci, Ira; R., Syahrul; Nursaid, Nursaid (Universitas Negeri Padang, 2016)
ABSTRACTÂ The purposeof this research is(1) to describe the mastering of vocabularies about environment, (2) describe the skills writing the argument composition about environment, and (3) analyze the correlation mastering of vocabularies about environment with argument composition writing skill about environment class X SMA Negeri 1 Ulakan Tapakis. The data of this research is to mastering of vocabularies about environment test score results and scores of argument composition writing skills test results. The findings of this research is (1) the mastering of vocabularies about environmentÂ on the qualified enough with an- average of 58.7 (2) the skills to argument composition writing about environment are more than enough qualified with an average of 73,33, and (3) based on the self-t, H1is accepted becauset count > t table is 4,49 > 1,70.Â Kata kunci: korelasi, penguasaan kosakata, argumentasi, lingkungan hidup, keterampilan